2013
DOI: 10.1016/s1734-1140(13)71075-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of the HIV protease inhibitor – saquinavir in differentiating human preadipocytes

Abstract: The results indicate that SQV affects not only metabolic (mitochondrial) activity of adipocytes, but affects the expression of genes related to differentiation and to a lesser extent to cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…These findings support earlier evidence in the literature where increased ROS levels or mitochondrial dysfunction were also observed individually upon treatment with type 1 HIV protease inhibitors (Estaquier et al 2002;Matarrese et al 2003;Roumier et al 2006;Chandra et al 2009;Touzet and Philips 2010;Bociąga-Jasik et al 2013;Xiang et al 2015), but it is the first time these parameters were measured simultaneously. The major advantage is that an unambiguous determination of both factors together in space and time allows pinpointing causal relationships.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings support earlier evidence in the literature where increased ROS levels or mitochondrial dysfunction were also observed individually upon treatment with type 1 HIV protease inhibitors (Estaquier et al 2002;Matarrese et al 2003;Roumier et al 2006;Chandra et al 2009;Touzet and Philips 2010;Bociąga-Jasik et al 2013;Xiang et al 2015), but it is the first time these parameters were measured simultaneously. The major advantage is that an unambiguous determination of both factors together in space and time allows pinpointing causal relationships.…”
Section: Discussionsupporting
confidence: 91%
“…HIV protease inhibitors (HIV PI) have been shown to induce increased basal ROS levels (Chandra et al 2009;Touzet and Philips 2010), and lowered antioxidant defenses (represented by lowered expression of SOD2 (Xiang et al 2015)). Independently, other reports have linked HIV PI to changed mitochondrial morphofunction (Estaquier et al 2002;Matarrese et al 2003;Roumier et al 2006;Bociąga-Jasik et al 2013;Xiang et al 2015). As a case study, we have used the established workflow to assess the effect of HIV PI on both parameters.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…PIs are toxic via different pathways, in particular by inducing mitochondrial dysfunction and oxidative stress and by promoting inflammation (Gougeon et al 2004;Caron et al 2007;Caron-Debarle et al 2010;Mencarelli et al 2012;Bociaga-Jasik et al 2013;Cassol et al 2013;Reyskens et al 2013). Several studies also reported that some PIs are able to induce ER stress in different types of cells (e.g., macrophages, adipocytes, hepatocytes) and tissues (e.g., liver, intestine) (Zhou et al 2005;Gupta et al 2007;Cao et al 2010;Touzet and Philips 2010;Wu et al 2010;Zha et al 2010Zha et al , 2013Br€ uning 2011;Zhou 2011;Br€ uning et al 2012;Apostolova et al 2013;Taura et al 2013;Wang et al 2013b).…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Saquinavir and its nitric oxide-derivative have been shown to trigger or foster apoptosis [22][23][24][25][26][27][28][29][30], an effect paralleled by inhibition of AKT-phosphorylation [22], downregulation of NF-κB [24,28,29], proteotoxic stress [22], endoplasmic reticulum stress [25], autophagy [25] and mitochondrial depolarization [31].…”
Section: Introductionmentioning
confidence: 99%